A Systematic Study of the Antibacterial Activity of Basidiomycota Crude Extracts - Marco Clericuzio; Mattia Bivona; Elisa Gamalero; Elisa Bona; Giorgia Novello; Nadia Massa; Francesco Dovana; Emilio Marengo; Elisa Robotti (MDPI AG, 2021)
The excessive consumption of antibiotics in clinical, veterinary and agricultural fields has resulted in tremendous flow of antibiotics into the environment. This has led to enormous selective pressures driving the evolution of antimicrobial resistance genes in pathogenic and commensal bacteria. In this context, the World Health Organization (WHO) has promoted research aiming to develop medical features using natural products that are often competitive with synthetic drugs in clinical performance. Fungi are considered an important source of bioactive molecules, often effective against other fungi and/or bacteria, and thus are potential candidates in the search of new antibiotics. Fruiting bodies of sixteen different fungal species of Basidiomycota were collected in the Italian Alps. The identification of fungal species was performed through Internal Transcribed Spacer (ITS) sequencing. Most species belong to genera Cortinarius, Mycena and Ramaria, whose metabolite contents has been scarcely investigated so far. The crude extracts obtained from the above mushrooms were tested for their inhibition activity against five human pathogens: Candida albicans ATCC 14053, C. glabrata ATCC 15126, Staphylococcus aureus NCTC 6571, Pseudomonas aeruginosa ATCC 27853 and Klebsiella pneumoniae ATCC 13883. Twelve crude extracts showed activity against P. aeruginosa ATCC 27853. Highest activity was shown by some Cortinarius species, as C. nanceiensis.